Kesantunan Berbahasa Mandailing dalam Tindak Tutur Direktif Anak Kepada Orangtuanya di Nagari Ujung Gading Kecamatan Lembah Malintang Kabupaten Pasaman - Yadi, Ahmad; Juita, Novia; Ngusman, Ngusman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this research was to describe the form directive speech acts, politeness principles, and the context of the speech of children to parents in a Mandailing language. Data of this research is direct speech conversation between a child and his parents. The source of data in this research is children and their parents is a native of the area. Data collected using recording techniques and the observation sheet (observation) and written technique as advanced techniques, then transcribed and analyzed. The findings of the research include three aspects, namely (1) the form of directive speech acts used by children to their parents in a Mandailing language is telling, suggesting, to instruct, challenge, and pleading, (2) the principles of linguistic politeness that are used by children to their parents in a Mandailing language is a maxim of generosity, the agreement, wisdom, and praise, and (3) context of the speech acts in the use of maxims by children to their parents in a Mandailing language maxim generosity is likely to be used for the purpose of telling. Topic of speech act usually talk every day, going home in a quiet atmosphere. Maxim agreements tend to be used for the purpose of suggesting and asking. Topic of speech act generally every day speech, occurred at home, in a quiet courtyard. Maxim wisdom and praise tends to be used for the purpose suggested. Topic of speech act usually talk every day, going home in a quiet atmosphere.